2017
DOI: 10.1108/sajbs-04-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of social entrepreneurial intention: an empirical study

Abstract: Purpose The purpose of this paper is to identify the role of cognitive styles (CgStys) and self-efficacy (SEff) in the formation of social entrepreneurial intentions (SEIs) among the students of a premier multi-campus technical university in India using the theory of planned behaviour as the research framework. Design/methodology/approach A 54-item questionnaire was responded by 550 students. The data were collected by employing a systematic random sampling method. In the total sample of the respondents, 67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 101 publications
(138 reference statements)
9
83
1
Order By: Relevance
“…Second determinant of the EI is PBC. The causal relation between of PBC and EI has also been found significant by previous studies such as Tiwari, Bhat, & Tikoria (2017). However, some studies such as Shah and Soomro (2017) reported this proposition (effect of PBC on EI) statistically non-significant.…”
Section: Proposed Theoretical Frameworkmentioning
confidence: 65%
See 3 more Smart Citations
“…Second determinant of the EI is PBC. The causal relation between of PBC and EI has also been found significant by previous studies such as Tiwari, Bhat, & Tikoria (2017). However, some studies such as Shah and Soomro (2017) reported this proposition (effect of PBC on EI) statistically non-significant.…”
Section: Proposed Theoretical Frameworkmentioning
confidence: 65%
“…Isiwu & Onwuka (2017) found that selfefficacy is a positive and significant predictor of AE and EI. The effect of SI on EI was also reported to be statistically significant by Ibrahima & Mas'udb (2016);Farrukh, et al (2017) and Tiwari, Bhat, & Tikoria (2017). Tiwari, Bhat, & Tikoria (2017) revealed that self-efficacy is a significant predictor of PBC and SN too.…”
Section: Proposed Theoretical Frameworkmentioning
confidence: 83%
See 2 more Smart Citations
“…Supporting this view, our first paper, "Predictors of social entrepreneurial intention: an empirical study" has explained the influence of cognitive styles and self-efficacy that encourage entrepreneurial intention. Because of the recent economic crisis and global recession, there is a social need to create value by utilizing resources in more innovative ways, naturally making way for emergence of new businesses (Tiwari et al, 2017). In order to start new businesses to jumpstart the economies, there is a need for both domestic and foreign resources.…”
Section: About the Current Papersmentioning
confidence: 99%